Reinterpreting Waqf Principles in The Digital and Sustainable Economy - Dyarini Mohammad, Anggia; Bayuni, Eva Misfah (Jurnal Manajemen, 2026)
Waqf, as an instrument of Islamic economics, is founded on strong normative principles, yet its implementation often remains limited to classical concepts. In the dynamic context of the modern economy, it is essential to develop innovative approaches to reconstruct waqf in terms of its objects, management, and intended purposes. This study aims to explore and analyse new interpretive spaces for the foundational principles of waqf, ranging from cash waqf and productive waqf to emerging ideas such as digital waqf, environmental waqf, and socio-ecological waqf. In addition to reviewing existing innovations that have been implemented in Indonesia and other countries, the study also proposes several novel approaches that remain underexplored both academically and in policy discourse, such as waqf for the circular economy, waqf for public technology, and the integration of waqf with community-based cooperative economics. Employing a qualitative approach, this research uses normative literature reviews and contemporary analysis of waqf practices in Indonesia. The findings suggest that there is significant potential for reinterpreting waqf principles through innovative approaches that align with the values of benefit perpetuity, trustworthy stewardship, and social orientation—recontextualized to meet the inclusive, participatory, and adaptive demands of the modern economy.